KONSEP DASAR MANAJEMEN SUMBER DAYA MANUSIA - Lutfi Aprilia; Nasywa Khairunisa; Hanifara Dyasti Rahayu; Machdum Bachtiar (STKIP Subang, 2026)
This research aims to explore the concept of performance management and reward strategies. The primary approach is a literature study, collecting data from books related to the definition, implementation, organization, and maintenance of human resources. Data analysis adopts the Miles and Huberman model, encompassing data reduction, data presentation, and conclusion drawing and verification. Therefore, this research forms an integral part of the discipline of Human Resource Management. Specifically, it outlines various fundamental theories and practical methods for managing the most valuable asset, human resources. This approach enables organizations to maximize employee contributions, thereby achieving their strategic goals more effectively, efficiently, and adaptively to changes in today's business environment.